Environmental stratification to model the potential impacts of climate change on Giant panda habitat in South-central China - Ralston, David (The University of Edinburgh, 2016)
AIM: To analyse the potential impacts of climate change on giant panda habitat based on a statistically derived Global Environmental Stratification (GEnS), using a range of CIMP5 global climate models (GCM) across four representative concentration pathways (RCP). LOCATION: Southern and central China (24 - 37 N and 94 - 110 E). METHODS: A supervised classification algorithm (random forests) was used to produce a statistically derived environmental stratification using a set of bioclimatic variables calculated for current climatic conditions and a set of GCMs. The classification procedure produced a set of environmental stratifications (n = 127) consisting of 75 strata which were aggregated into 13 bioclimatic zones. Geospatial analysis techniques were utilised to identify the extent of environmental change over the current panda geographic range in response to climate change. RESULTS: Future climate stratifications predict significant changes to the areal extent and elevation range of GEnS strata and bioclimatic zones. By 2070, the areal extent of bioclimatic zones in the current habitat range are projected to change by 1167km2 on average. Equally, the mean elevation change is projected to shift on average by 363m. Zones which currently lie at high elevations will see significant reductions in area, whereas lower elevation zones will expand. MAIN CONCLUSIONS: The analysis indicates that projected climate change may result in significant environmental change to the giant panda’s current geographical range. These impacts are likely to effect the distribution of panda habitat in the near future. Conservation strategies must incorporate possible climate change impacts in order to adapt and move reserves to more suitable areas.
Keywords: Bioclimatic indicators, Climate change, Environmental stratification, Giant panda habitat, Conservation strategies; Bioclimatic indicators; Climate change; Environmental stratification; Giant panda habitat; Conservation strategies